LaSiO3Cl:Ce3+,Tb3+ and Mg2TiO4:Mn4+: quantum dot phosphors for improving the optical properties of WLEDs - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this research, we focus on the solutions to enhance the lighting properties as well as the heat regulation of the white light-emitting diodes (WLEDs) with conventional phosphor and quantum dots (QDs). Although receiving lots of attention for being an innovative lighting solution with good color rendering index, the potentials of WLEDs conjugated with quantum dots (QDS), especially the QDs-phosphor mixed nanocomposites ones, are restrained due to the lacking performance in the aspects mentioned above. The crucial requirement to produce better WLEDs is finding solutions that improve the lacking aspects, therefore, through observing previous studies and applying advanced technique, this research suggest an effective and unique packaging configuration, in which the nanocomposites QDs-phosphor layer is set horizontally to the WLED. This novel packaging configuration allow WLED performance in terms of lighting and heating to reach it peaks. This is the first time four different types of WLEDs, single-layer phosphor, dual-layer remote phosphor with yellow-red and yellow-green, and triple-layer phosphor, were simulated, utilized and compared in one study to decide the best WLED configuration. The results show that the triple-layer phosphor configurations improve the color rendering ability and lumen output better than the other configurations.